2007
DOI: 10.1021/bi702004b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interplay in the Mechanism of Partial Agonist Activation in α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid Receptors

Abstract: Abstractα-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, one subtype in the family of ionotropic glutamate receptors, are the main receptors responsible for excitatory signaling in the mammalian central nervous system. Previous studies utilitizing the isolated ligand binding domain of these receptors have provided insight into the role of specific ligand-protein interactions in mediating receptor activation. However, these studies relied heavily on the partial agonist kainate, in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Interestingly, Fourier transform infrared resonance spectroscopy measurements at pH 7.4 suggest that the bound form is protonated based on difference spectra for the ligand carbonyl vibrations (V. Jayaraman, personal communication). 62,63 If this is the case for all the ligands examined in the present study, then the R ex and Î data may indicate that the willardiines bind stably to sites in lobe 1 on the NMR timescale but give rise to significant μs-ms timescale dynamics at the ligandlobe 2 interface for the less potent forms.…”
Section: Ligand-binding Site and Peptide Flip Regionmentioning
confidence: 74%
“…Interestingly, Fourier transform infrared resonance spectroscopy measurements at pH 7.4 suggest that the bound form is protonated based on difference spectra for the ligand carbonyl vibrations (V. Jayaraman, personal communication). 62,63 If this is the case for all the ligands examined in the present study, then the R ex and Î data may indicate that the willardiines bind stably to sites in lobe 1 on the NMR timescale but give rise to significant μs-ms timescale dynamics at the ligandlobe 2 interface for the less potent forms.…”
Section: Ligand-binding Site and Peptide Flip Regionmentioning
confidence: 74%
“…However, there were several structures such as those of the glutamate-bound form of the T686A mutant and the structures of the AMPA bound form of the L650T mutant that do not follow this trend (22,(25)(26)(27). Ensemble FRET investigations with the wild type and L650T mutant were consistent with the x-ray structures, further validating these deviations from the cleft closure hypothesis (28,29).…”
mentioning
confidence: 74%
“…The efficacies are taken from Jin et al (5) and Mankiewicz et al (12) and are relative to the full agonist, glutamate. When a given agonist was tested in both studies, the average value was used and the standard error of the mean shown as the error bar.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…In addition to the crystal structures, the internal dynamics of each lobe have been studied with NMR spectroscopy (811) and the relative strengths of hydrogen bonds have been accessed with FTIR (1214) and NMR (9) studies. The overall picture is that Lobe 1 (Figure 1) is relatively rigid on the μs-ms timescale, with Lobe 2 exhibiting characteristic internal motions that vary between full and partial agonists (811).…”
mentioning
confidence: 99%